Wrapped in the flag of Israel : Mizrahi single mothers and bureaucratic torture - Lavie, Smadar (Expanding frontiers., 2018)
Weaving together memoir, auto-ethnography, political analysis, and cultural critique, Lavie equates bureaucratic entanglements with pain--and, arguably, torture--to examine the conundrum of loving and staying loyal to a state that repeatedly inflicts pain on its non-European Jewish women citizens.